The change of the Weierstrass structure under one row perturbation. Issue 6 (26th January 2022) - Baragaña, Itziar; Roca, Alicia
Abstract: In this work we study the change of the structure of a regular pencil when we perform small perturbations over some of its rows and the other rows remain unaltered. We provide necessary conditions when several rows are perturbed, and prove them to be sufficient to prescribe the homogenous invariant factors or the Weyr characteristic of the resulting pencil when one row is perturbed.